ChemInform Abstract: C—O Cross‐Coupling of Activated Aryl and Heteroaryl Halides with Aliphatic Alcohols. Issue 6 (20th February 2013) - Maligres, Peter E.; Li, Jing; Krska, Shane W.; Schreier, John D.; Raheem, Izzat T.
Abstract The title reaction is performed with palladium/Josiphos‐type ligand catalyst systems and primary, secondary, or tertiary alcohols without the need for an excess of either coupling partner and preformation of the catalysts.